Ke Arah Paradigma Baru Pendidikan Islam: Telaah Pemikiran Transformatif Amin Abdullah, Perspektif Filsafat Pendidikan : Penelitian - Hasan Maftuh Hasan; Saadi Saadi; M. Aji Nugroho; Badrus Zaman (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This study analyzes Amin Abdullah's paradigm of integration-interconnection of Islamic knowledge as a post-reformation Islamic reform that bridges the dichotomy of religious knowledge and science through a holistic and contextual approach. The study uses qualitative methods with a philosophical-hermeneutic approach through analysis of texts, academic documents, and interviews with academics to examine its implementation in educational practice. The results show that this paradigm is not only theoretical, but has been manifested in the curriculum, academic culture, and development direction of UIN Sunan Kalijaga. Philosophically and epistemologically, this paradigm transforms Islamic education to be more inclusive, dialogical, and applicable by combining Islamic values, scientific rationality, and empirical experience, and viewing Islamic education as an open system that is responsive to social realities and the development of modern science. The study concludes that the integrative-interconnective paradigm is an important foundation for Islamic educational philosophy that is relevant to global challenges and in harmony with various schools of educational philosophy in shaping the whole person.